PENERAPAN PjBL UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PADA WORKSHOP PENDIDIKAN MATEMATIKA - Alfiana Rahmawati; Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The low level of creativity development is caused by learning in class that is trained by knowledge, memory, logical thinking ability. Learning is expected to solve these problems is through by PjBL (Project Based Learning). Especially in the Mathematics Education Workshop which requires students to have creativity in making educational props. The problem in this research is Does learning using PjBL (Project Based Learning) can improve students' creative thinking in Mathematics Education Workshop? The purpose of this research is to know the improvement of students' creative thinking ability through learning using PjBL (Project Based Learning) in Mathematics Education Workshop. This research uses quantitative descriptive method with questionnaire data collection and observation. Based on the results of research and data analysis conducted by researchers, showed the influence of  application of PjBL (Project Based Learning) to the creative thinking ability is 48%. The conclusion of this research is application of PjBL (Project Based Laerning) have an effect on student creative thinking ability. Suggestions is this research can expected to continue so can be developed on other factors that can improve students' creativity thinking ability. Keywords: project based learning, creaytive thinking ability